2007
DOI: 10.1108/00251740710819069
|View full text |Cite
|
Sign up to set email alerts
|

Transaction costs in group microcredit in India

Abstract: Existing literature indicates that transaction costs are a major contributor to high interest rates on microcredit loans. A study was conducted using the case study method in order to examine the transaction costs of three established microfinance institutions. Transaction cost includes the costs of group formation, training, appraisal, documentation, disbursement and monitoring. First year and repeat loan transaction costs were studied. Life cycle transaction costs, namely the costs over the group's life cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 5 publications
1
52
0
Order By: Relevance
“…The reason is that distances are longer and population densities are lower, making it more time and fuel consuming for banks to approach and to monitor borrowers (Armendáriz de Aghion and Morduch, 2010;Caudill et al, 2009). Collection costs are considered to be one of the largest operational cost components in microfinance (Shankar, 2007). Here, grace periods increase the time period that loan amounts are outstanding and, hence, lead to higher interest returns for the MFI, contributing to compensate for higher operational costs.…”
Section: Lending Principles In Microfinancementioning
confidence: 99%
“…The reason is that distances are longer and population densities are lower, making it more time and fuel consuming for banks to approach and to monitor borrowers (Armendáriz de Aghion and Morduch, 2010;Caudill et al, 2009). Collection costs are considered to be one of the largest operational cost components in microfinance (Shankar, 2007). Here, grace periods increase the time period that loan amounts are outstanding and, hence, lead to higher interest returns for the MFI, contributing to compensate for higher operational costs.…”
Section: Lending Principles In Microfinancementioning
confidence: 99%
“…In their paper on managing the linkage between export development and poverty reduction, Skae and Barclay (2007) seek to remedy that situation, by proffering a management framework through which the linkage between exports and poverty reduction can be better understood and strengthened. We then move to several specific examples, in the form of case studies from Brazil (Barin- Cruz, et al, 2007), Malawi and Ethiopa (Duke and Long, 2007), and India (Shankar, 2007).…”
Section: Implementation: a Framework For Action And Examplesmentioning
confidence: 99%
“…Both have been criticised as well as praised, by both ends of the political spectrum (cf Neff, 1996;Tucker, 2006). One area of criticism, high interest rates on microcredit loans and the transaction costs that contribute to them, has been examined by Shankar (2007), with a view to being able to draw implications on how lending rates in microcredit could be reduced in a sustainable manner. Shankar (2007) studied three established microfinance institutions in India to determine the composition of transaction costs, and found that the key drivers of direct transaction costs are field worker compensation and the number of groups handled per field worker, with collection activity as the single largest contributor.…”
Section: Implementation: a Framework For Action And Examplesmentioning
confidence: 99%
See 2 more Smart Citations